Studi atas Zikir Tarekat Masyarakat Urban Jemaah Tarîqah Qâdirîyah Naqshabandîyah di Jakarta - Hafil, Ach. Shodiqil (MarÃ¢ji`: Jurnal Ilmu Keislaman, 2014)
This article seeks to know the practice of dhikr ritual in Qâdirîyah wa Naqshabandîyah Tariqa that is practiced by the Jakarta urban society. Furthermore, how the community interpret and understand the values of dhikr in the Tariqa. The results of this study indicate that the practice of dhikr in Qâdirîyah wa Naqshabandîyah Tariqa conducted by some of Jakarta urban society is by combining two techniques of dhikr of Allah, the jahr recitation (orally and with loud voice) and the khafî zikr (with heart and silently). Besides, Jakarta urban society that follow the Qâdirîyah wa Naqshabandîyah Tariqa interpret dhikr with various arguments. The deeper of knowledge had by the followers of the Tariqa, the deeper of interpretation they will have. Adherents of the Tariqa who have higher level of knowledge do not interpret the practice of dhikr only as sensory motivations, but rather spiritual obligations oriented to togetherness and closeness with God.